Chapter Reading to reveal the world - Lukić, Jasmina (Amsterdam University Press, 2023)
Following the critical principles as they were articulated in an earlier article on South African literature (Buikema, 2009), the paper discusses a more recent call for literary engagement in the context of contemporary debates on world novel and world literature. In a dialogue with Buikema's reading of two South African novels, Disgrace by J.M. Coetzee and Agaat by Marlene van Niekerk, the paper turns to Octavia Butler's novel Kindred (1979) following a similar method of interpretation, which emphasizes the singularity of text and combines close reading with contextual approach.